(untitled) (Scientific journal of the Fergana State University, 2024)
Among insects, dragonflies occupy a special place in biocenoses and the ecosystem as a whole with their morphological and biological characteristics. According to the latest information, about 6,000 species of dragonflies are currently known. They are the oldest group of arthropods. These insects appeared 300 million years ago, that is, dragonflies are known from the Stone Age. Different from other insects, it is highly adapted to the environment with its morphological features. Specialization is observed in two directions, i.e. air and water environment. If adult dragonflies are adapted to live in the air; their larvae in the aquatic environment. So, in the development of dragonflies, developmental processes alternate. Due to the development of dragonflies in two different environments, they make a great contribution to the exchange of substances in biogeocenoses. Even in small water bodies, they participate in the formation of several tons of biogenic substances during a year.